1994
DOI: 10.1007/bf00403381
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of acetaminophen interference in glucose sensors by a composite Nafion membrane: demonstration in rats and man

Abstract: Amperometric glucose sensors typically monitor the production of hydrogen peroxide generated in the course of the enzymatic oxidation of glucose. At the applied potential necessary to oxidize the peroxide produced, other species are also electroactive and contribute to the signal. Interference of ascorbate or urate has been effectively eliminated, but that resulting from the widely used analgesic acetaminophen is not. The aim of this work was to reduce this interference, which was found to be possible by intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 14 publications
0
29
0
1
Order By: Relevance
“…Synthetic polymer membranes, such as PU, Nafion, polytetrafluoroethylene, polyethylene glycol (PEG), hydrogels and poly-L-lactic acid, have been confirmed to expand detection range and increase biocompatibility of glucose sensors [18][19][20]. Studies have shown that Nafion and hydrogel have the advantages of enhancing hydration, reducing immune cell adsorption and fibrosis, but also show defects such as more prone to expansion or mineralization [21][22][23][24][25][26]. Therefore, only PU and its modified polymers have been widely used as commercially restriction membranes for glucose transmission with improved linearity [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic polymer membranes, such as PU, Nafion, polytetrafluoroethylene, polyethylene glycol (PEG), hydrogels and poly-L-lactic acid, have been confirmed to expand detection range and increase biocompatibility of glucose sensors [18][19][20]. Studies have shown that Nafion and hydrogel have the advantages of enhancing hydration, reducing immune cell adsorption and fibrosis, but also show defects such as more prone to expansion or mineralization [21][22][23][24][25][26]. Therefore, only PU and its modified polymers have been widely used as commercially restriction membranes for glucose transmission with improved linearity [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…49 Prior studies have shown that acetaminophen interference can be eliminated when PFSA is used as an inner membrane. 50, 51 For our glucose sensor, PFSA was used as an outer membrane and it was necessary to determine if this structure can also block interference molecules. The arrows in Figure 6 (a) indicate when 0.13 mM of acetaminophen was added to the electrolyte at the end of the experiment.…”
Section: Resultsmentioning
confidence: 99%
“…7 As the research for 1,5-AG detection is preliminary, replicates of detection in complex solutions may yield better accuracy in higher concentrations of blood, requiring only dilution in the final device architecture rather than the use of embedded molecular recognition elements or nonspecific binding protective coatings. 8 As it can be seen in Figure 1, the optimal binding frequency for a particular sensor may not be a single frequency, but rather a range of frequencies with an optimal plateau. Only a more narrow range can be found by evaluating more sensors and determining the average.…”
Section: Discussionmentioning
confidence: 99%